THE EFFECTIVENESS OF PICTURE SEQUENCETOWARDSSTUDENTS’ ABILITY IN USING CONJUNCTION AT THE EIGHT GRADE OF MTs NEGERI MODEL KOTA SORONG IN THE ACADEMIC YEAR 2016/2017 - Wibowo, Ari; Nursalim, Nursalim; Astuti, Yuli (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
Learning writing is one of fourth skill of learning second language that must be mastered by students. For this reason the writers want to investigate and conduct the study in this field. The Statement of Problem “Is Picture Sequence effective towards students' ability in using conjunctionat the eight grade of MTs. Negeri Model Kota Sorong in the academic year 2016/2017?” the research design in this investigation is experimental research. The population of this study is students in MTs. Negeri Model Kota Sorong and has taken as sample were class VIII-G as a control group and VIII-D as the experimental group. In this study, the writer applies some steps for conducting the experiment, they were: observation, planning, treatment, and post-test. It was conducted in three meetings. To collect the data of this study, the writer using writingtest. Post-test was conducted to both of groups to see the differences between control and experimental groups and also to prove the writer’s hypothesis that picture sequences can give an impact to the students’ achievement instudents’ ability of using conjunction in writing. By using t-test formulation the writer gets value of t-observe 2.178 and the t-critical 0.05 is 2.021 It means that t-obs value is higher than the t-crit. In other word, it can be said that the alternative hypothesis ( H1) is accepted and null hypothesis (H0) is rejected, or it can be said that picture sequences as method that effective and applicable at the eighth grade of MTs. Negeri Model Kota Sorong towards students’ ability of using conjunction in writing narrative text.